The Implementation of Peace Education Values in Surah Al-Hujurat Verses 9–10 in Islamic Educational Environments - Siregar, Amelia Zahra A; Irsan, Lutfiah Marsya; Zidansyah, Muhammad (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the implementation of peace education values contained in the Qur’an, particularly in Surah Al-Hujurat verses 9–10, within Islamic educational environments. These values include conflict resolution, brotherhood, justice, and peace, which serve as essential foundations for character development among students. This research employed a qualitative approach with a descriptive study method. The participants included teachers and students in Islamic educational institutions. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that peace education values have been implemented through classroom learning, social interactions, and the cultivation of tolerance and mutual respect within the school environment. However, several challenges were identified, including limited in-depth understanding of the verses and a lack of innovative teaching methods. This study concludes that the implementation of peace education values in Surah Al-Hujurat verses 9–10 plays a crucial role in shaping students’ harmonious character and moral development.